PENGARUH PENGGUNAAN BEBERAPA MULSA PLASTIK dan VARIETAS TERHADAP SERANGAN PENYAKIT ANTRAKNOSA (Colletotrichum capsicii Sydow.) PADA TANAMAN CABAI (Capsicum annum L.) di LAPANGAN - Charles E Ginting 1; Mukhtar Iskandar Pinem; Maryani Cyccu Tobing (Jurnal Agroekoteknologi, 2013)
he influence of the use of plastic mulchs and chili varieties on the attack of  antracnose(Colletotrichum capsicii Sydow.) on chili plants (Capsicum annum L.) in the field.                                                                                                                       The aim of the research was to know the appropriate type of  mulchs which could be used to curbthe attack of antracnose and which chili varieties are  resistant against antracnose. The researchused  Cluster  Random  Design (CRD) Factorial which consisted of two factors and threerepetitions. The first factor was plastic mulchs: non mulch (M0). silver (M1). and black (M2) the second factor was varieties: Lado F1 (V1). Lembang 1 (V2). Tanjung 2 (V3). The resultshowed that silver black mulch was the best to inhibite antracnose (1.08 %) with Lado F1(1.12%) and the highest on no mulch (7.82 %) with Tanjung 2. Interaction of no mulch andTanjung 2 were lowest (1.70%) and the highest (11.46%) on no mulch and Tanjung 2. Thehighest production  (0.72 ton/ha) on silver black mulch with Lado F1 (0.63 to/ha) and the loweston no mulch (0.20 ton/ha) with Tanjung 2 (0.17 ton/ha). Interaction of black silver mulch andLado F1 were highest (0.89 ton/ha) and the lowest (0.15 ton/ha) on no mulch and Tanjung 2. Keywords : plastic mulchs. varieties. antracnose. chili.